COMPARISON OF A STIMULUS EQUIVALENCE PROTOCOL AND TRADITIONAL LECTURE FOR TEACHING SINGLE-SUBJECT DESIGNS - Lovett, Sadie; Rehfeldt, Ruth Anne; Garcia, Yors; Dunning, Johnna (Journal of applied behavior analysis, 2011)
This study compared the effects of a computer‐based stimulus equivalence protocol to a traditional lecture format in teaching single‐subject experimental design concepts to undergraduate students. Participants were assigned to either an equivalence or a lecture group, and performance on a paper‐and‐pencil test that targeted relations among the names of experimental designs, design definitions, design graphs, and clinical vignettes was compared. Generalization of responding to novel graphs and novel clinical vignettes, as well as the emergence of a topography‐based tact response after selection‐based training, were evaluated for the equivalence group. Performance on the paper‐and‐pencil test following teaching was comparable for participants in the equivalence and lecture groups. All participants in the equivalence group showed generalization to novel graphs, and 6 participants showed generalization to novel clinical vignettes. Three of the 4 participants demonstrated the emergence of a topography‐based tact response following training on the stimulus equivalence protocol.